2020
DOI: 10.1101/2020.10.06.327288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ablation of Proliferating Osteoblast Lineage Cells After Fracture Leads to Atrophic Nonunion in a Mouse Model

Abstract: Nonunion is defined as the permanent failure of a fractured bone to heal, often necessitating surgical intervention. Atrophic nonunions are a subtype that are particularly difficult to treat. Animal models of atrophic nonunion are available; however, these require surgical or radiation induced trauma to disrupt periosteal healing. While these approaches can result in nonunion, such invasive methods are not representative of many clinical nonunions where osseous regeneration has been arrested by a “failure of b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…A 3.6Col1A1‐tk mouse model 65 was created in which pretreatment with the nucleoside analog ganciclovir for 14 days resulted in the ablation of replicating osteoblast progenitors. A study in our lab fractured these 3.6Col1A1‐tk mice and observed that arresting proliferating osteoblast‐lineage cells for at least 2 weeks after fracture resulted in blunted formation and remodeling of mineralized callus leading to a functional atrophic nonunion 66 . Overall, extensive research has targeted the creation of animal models for nonunions, specifically atrophic nonunions, to improve treatment and overall clinical outcomes.…”
Section: In Vivo Models Of Bone Defectsmentioning
confidence: 99%
“…A 3.6Col1A1‐tk mouse model 65 was created in which pretreatment with the nucleoside analog ganciclovir for 14 days resulted in the ablation of replicating osteoblast progenitors. A study in our lab fractured these 3.6Col1A1‐tk mice and observed that arresting proliferating osteoblast‐lineage cells for at least 2 weeks after fracture resulted in blunted formation and remodeling of mineralized callus leading to a functional atrophic nonunion 66 . Overall, extensive research has targeted the creation of animal models for nonunions, specifically atrophic nonunions, to improve treatment and overall clinical outcomes.…”
Section: In Vivo Models Of Bone Defectsmentioning
confidence: 99%